Arabs And "Indo-arabs" In Indonesia: Historical Dynamics, Social Relations And Contemporary Changes - Qurtuby, Sumanto Al (Penerbit Universiti Sains Malaysia (USM Press), 2017)
This article outlines the origins, development and historical dynamics of Arabs in Indonesia and discusses responses of Indonesians, particularly Muslims, towards this group. It sketches a variety of Indonesia's Arabs—sadah and non-sadah alike— and their contributions to the shape of Indonesian Islam, Islamic cultures and Muslim politics. It also traces the roots of—and depicts the historical dynamics and changes—social relations and interactions between Arabs and local populations. The relations between Arabs and non-Arabs in the country have always been marked with conﬂict and tensions on the one hand, and peace and cooperation on the other. Some Muslims in the country "have admired" and built a strong relationship with the Arabs and "Indo-Arabs" while others have denounced them as the destroyers of Indonesia's local traditions, civic pluralism, social stability and interreligious tolerance. This article tries to portray this paradox, discuss factors contributing to the damaging image of Arabs in contemporary Indonesia, and explain the rationales behind it. Lastly, it discusses prospects and the possibilities of the constructive relationships between Arabs, Indo-Arabs, and other nationals, social groupings, and ethnicities in the country.